CP-024 Pharmaceutical interventions with zolpidem in elderly patients. (14th February 2016) - Navarro, M; Plasencia, I; Betancor, T; Ramos, E; Gomez, E; Morales, A; Ocaña, A; Callejon, G; Merino, J; Fraile, C
Abstract : Background: The use of hypnotic drugs in elderly patients has been associated with a higher risk of somnolence and somnambulism. Many patients had been treated with zolpidem. Purpose: Therefore, the AEMPS published an alert in March 2014 recommending that the highest dose used in patients >65 years should be 5 mg/day. The aim of our study was to evaluate if this recommendation was accomplished in our hospital and the effect of pharmaceutical intervention. Material and methods: Cross sectional study that included all patients >65 years old who were receiving treatment with zolpidem on 3 April 2015. Dose of zolpidem and presence of pharmaceutical intervention was obtained using electronic clinical history (SELENE) and the pharmacy service managing software (Farmatools). Results: 385 patients were >65 years of age. 3.4% of them (13 patients) had zolpidem in their prescription (100% as chronic treatment). 84.6% had 10 mg/day (a higher dose than the recommendations). In 15.4% of cases, there was a pharmaceutical intervention recommending reducing the dose to 5 mg/day; 50% of these recommendations were accepted. Conclusion: The majority of patients had an inappropriate dose according to the AEMPS recommendations. The number of pharmaceutical interventions was low and the acceptance rate, although higher, was insufficient. Therefore, more education for pharmacists and the medical team (including primary care) has to be made in order to improve the management of hypnotic drugs in the elderly population. References and/or Acknowledgements: AEMPS ALERT No conflict of interest.